S132 A randomised controlled study of lung cancer screening in scotland using the detection of autoantibodies to tumour antigens (earlycdt-lung test). (15th November 2016) - Dorward, A; Mair, F Frances; Sullivan, F; Vedhara, K; Kendrick, D; Treweek, S; McCowan, C; McConnachie, A; Sproule, M; Briggs, A; Ritchie, L; Milroy, R; et al.
Abstract : Background: EarlyCDT®-Lung Test detects autoantibodies to abnormal cell surface proteins from the early stages of lung cancer with a specificity of 93%. This may allow earlier tumour detection thus altering prognosis. The primary research question is: Does using the EarlyCDT®-Lung Test to identify those at high risk of lung cancer, followed by xray and CT scanning in the test positive group, reduce the incidence of patients with late-stage lung cancer (III and IV) or unclassified presentation (U) at diagnosis, compared to standard practice? Recruitment was completed in June 2016 with 12, 018 subjects randomised. Methods: A RCT in Scotland recruiting from the most socially disadvantaged quintiles. Adults aged 50 to 75 (ECOG 0–2) who were at high risk for lung cancer (>20 pack years or relevant family history) were eligible. The intervention was the EarlyCDT®-Lung Test, followed by chest xray and CT in those with a positive result. The comparator is standard clinical practice in the UK. The primary outcome is the difference, after 24 months, between the rates of patients with stage III, IV or unclassified lung cancer at diagnosis in test v no-test group. Secondary outcomes include: all-cause mortality; cancer specific mortality; a range of morbidity outcomes; cost-effectiveness and measures examining the psychological and behavioural consequences of screening. Participants with a positive test result had an initial chest xray which was used to determine the urgency and the need for contrast in the initial screening CT. Those in whom the initial CT scan did not lead to a lung cancer diagnosis were offered biannual chest CTs for 24 months. Participants who are found to have lung cancer will be followed-up to assess both time to diagnosis and stage of disease at diagnosis. Results: 575/6120 (9.8%) of the test group had a positive test with 207 found to have lung nodules >8 mm, 16 cancers have been detected so far, 12 of which are at early stage. Eleven have abnormalities undergoing current investigation. At this stage of the trial we have no outcome data for the comparison group. Conclusion: The study will determine EarlyCDT-Lung test's clinical and cost effectiveness.